Management Information Systems and its Impact on Improving the Entrepreneurship of Duhok Polytechnic University: an Exploratory Study for the Organizations of Duhok Polytechnic University (Al-Mansour Journal, 2023)
The research aims to demonstrate the success of the information system and its role in improving the entrepreneurship of the Duhok Polytechnic University, an exploratory study of the opinions of a sample of the university organizations in the center of the Duhok city. and the researchers relied on this to adopt a basic problem: What is the role of the success of the management information system in developing the entrepreneurial characteristics in the Technical College of Administration and the Technical Institute of Administration in Dohuk, and the researchers adopted a main hypothesis: The process of success of management information systems plays a key role in improving the entrepreneurial characteristics of the organizations surveyed. The researchers also relied on the descriptive survey method for the opinions of a sample of human resources working in the sample surveyed, numbering (42) individuals, by designing a questionnaire that included questions describing the independent variable (the success of the Management Information Systems) and the number of questions about it (16 questions), while the number of questions related to the dependent variable (Entrepreneurial Characteristics) reached 10 questions. The researchers also relied, in describing and diagnosing research variables, and analyzing the results on some indicators and statistical methods, including percentages, weighted mean, deviation standard, correlation coefficient and straight regression equation, the research reached a main result: the success of the management information system affects the entrepreneurial characteristics by 0.396 times, according to the value of the coefficient of determination.
Keywords: Management information systems; Entrepreneurial characteristics; Duhok Polytechnic University